Outcome and determinants of failure to complete primary R‐CHOP treatment for reasons other than non‐response among patients with diffuse large B‐cell lymphoma. Issue 7 (3rd April 2020) - Wästerlid, Tove; Harrysson, Sara; Andersson, Therese M.‐L.; Ekberg, Sara; Enblad, Gunilla; Andersson, Per‐Ola; Jerkeman, Mats; Eloranta, Sandra; Smedby, Karin E.
Abstract: Patients with diffuse large B‐cell lymphoma (DLBCL) who fail to complete planned treatment with R‐CHOP due to toxicity are sparsely described. We investigated the extent of failure to complete treatment (six cycles or more, or three cycles + RT for patients with stage I disease) with R‐CHOP for reasons unrelated to non‐response, the determinants of such failure and the outcome among these patients. Three thousand one hundred and forty nine adult DLBCL patients who started primary treatment with R‐CHOP were identified through the Swedish lymphoma register 2007‐2014. Of these, 147 (5%) stopped prematurely after 1‐3 cycles of R‐CHOP for reasons unrelated to non‐response, 168 (5%) after 4‐5 cycles and 2639 patients (84%) completed planned treatment. Additionally, 195 (6%) patients did not complete treatment due to non‐response or death before treatment end. In a multivariable logistic regression model, age > 75 years, poor performance status, extranodal disease and Charlson Comorbidity Index ≥1 were significantly associated with failure to complete planned R‐CHOP treatment for other reasons than non‐response. Non‐completion of treatment strongly correlated with survival. Five‐year overall survival for patients who received 1‐3 cycles was 26% (95% CI: 19%‐33%), 49% (95% CI: 41%‐57%) for 4‐5 cycles and 76% (74%‐77%) for patients who completed treatment. Failure to complete planned R‐CHOP treatment is an important clinical issue associated with inferior survival. Old age and poor performance status most strongly predict such failure. These results indicate a need for improved treatment tailoring for patients with certain baseline demographics to improve tolerability and chance for treatment completion.